Striving for Equity and Efficiency : An Assessment of Provider Payment Reforms in the Philippines Health Sector - World Bank (World Bank, Washington, DC, 2018)
This report reviews the current provider payment arrangements and policies of the Philippines, and the extent to which they have contributed to the achievement of the HFS goals. It focuses on the pillars of the HFS that center on provider payment issues, including what is paid for and by whom (pillar 3) and how it is paid for (pillar 4). Because the HFS envisages that pooled sources of health funding, such as payments by the Philippines Health Insurance Corporation (PHIC or PhilHealth) and the government budget, should progressively replace OOP spending as the source of financing for health care, the extent to which this shift has occurred is a recurring theme. In addition, the assessment looks at how the purchasing arrangements improve allocative and technical efficiency, equity, and quality. It takes a sectoral approach to purchasing, looking not only at the purchasing arrangements of PhilHealth, but also purchasing of health services by the DOH and local government units (LGUs). The assessment concludes with concrete recommendations for the next five years and beyond.